Antithrombotic Therapy in Carotid Artery Disease - Papanikolaou, Paraskevi; Antonopoulos, Alexios S.; Mastorakou, Irene; Angelopoulos, Andreas; Kostoula, Efthalia; Mystakidi, Xara-Vasiliki; Simantiris, Spyros; Galiatsatos, Nikolaos; Oikonomou, Evangelos; Tousoulis, Dimitris (Current Pharmaceutical Design, 2020)
The management of asymptomatic atherosclerotic carotid artery disease and the role of antithrombotic therapy is of increasing importance for stroke prevention. Non-invasive imaging of carotid plaques can identify high-risk plaque features that are associated with the risk of plaque rupture. Carotid plaque necrosis, hemorrhage, fibrous cap thinning, and the presence of foam cells have all been correlated with the risk of rupture and onset of neurological symptoms in patients with carotid stenosis. Antiplatelets are currently recommended for patients with a history of ischemic stroke and/or significant carotid artery stenosis, with aspirin and clopidogrel being the most widely used and studied agents. The role of dual antiplatelet therapy remains controversial. Moreover, there is scarce evidence on the role of newer anticoagulant agents in stable patients with carotid artery stenosis. In this review article, we discuss the pathophysiology of carotid atherosclerosis, the use of non-invasive imaging for detecting the vulnerable carotid plaque and summarize the existing clinical evidence on the use of antiplatelet and antithrombotic agents in carotid artery disease.
Keywords: carotid artery disease